A Newborn with Major Congenital Anomalies of Amniotic Band Syndrome Associated with Acyanotic Congenital Heart Disease VSD, Oral Facial Cleft and Hdyrocephalus: A Case Report - Komba, Nicodem; Benjamin, Erica; Yatera, Hashim; Mdoe3, Mwajuma; Chubi, Mwanaheri; Luoga, Simoni; Msemo, Hawa (Women, Midwives and Midwifery, 2026)
Background: congenital anomalies are structural or functional anomalies that occur during intrauterine life and might be identified before, at birth or later in life. An estimated 6% of babies worldwide are born with a congenital disorder, resulting in 17% to 42% deaths among infants and 20% to 30% of stillbirths. In Tanzania, its prevalence is estimated to be 60.5 per 1000 live births. Majority of these are due to multifactorial including chromosomal anomalies. Its impact in our African societies extends to social consequences including stigmatization, divorce and witchcraft suspicions. Case Presentation: we present a case report of syndromic baby with major congenital malformation associated with Oral facial cleft, Congenital hydrocephalus, Acyanotic congenital heart disease VSD, Amniotic band syndrome on left lower limb and fingers of upper limbs. This is the first case to be reported in Tanzanian Context